The Concept of “Genetic Responsibility” and Its Meanings: A Systematic Review of Qualitative Medical Sociology Literature - Leefmann, Jon; Schaper, Manuel; Schicktanz, Silke (Frontiers in Sociology, 2017)
The acquisition of genetic information (GI) confronts both the affected individuals and health-care providers with difficult, ambivalent decisions. Genetic responsibility (GR) has become a key concept in both ethical and socio-empirical literature addressing how and by whom decision-making with respect to the morality of GI is approached. However, despite its prominence, the precise meaning of the concept of GR remains vague. Therefore, we conducted a systematic literature review on the usage of the concept of GR in qualitative, socio-empirical studies, in order to identify the main interpretations and to provide conceptual clarification. The review identified 75 studies with primarily an Anglo-American setting. The studies focused on several agents: the individual, the family, the parent, the health-care professional and the institution and refer to the concept of GR on the basis of either a rational/principle-oriented approach or an affective/relational approach. A subtype of the rational/principle-oriented approach is the reactive approach. The review shows how the concept of GR is useful for analyzing and theorizing about socio-empirical findings within qualitative socio-empirical studies, but also reveals conceptual deficits in terms of insufficient theoretical accuracy and heterogeneity, and in the rarity of reflection on cultural variance. The vagueness and multiplicity of meanings for GR in socio-empirical studies can be avoided by more normative-theoretical explication of the underlying premises. This would provide a higher degree of differentiation of empirical findings. Thereby, the complex findings associated with the individual and social implications of genetic testing (GT) in empirical studies can be better addressed from a theoretical point of view, and can subsequently have a stronger impact on normative and policy debates.